Hitching a ride: Vector feeding and virus transmission - Stafford, Candice A. (Landes Bioscience, 2012)
The majority of plant viruses rely on insect vectors for transmission. Insects with piercing-sucking mouthparts are the most common and efficient vectors because, they are able to inject viruses into specific plant tissues. Acquisition and inoculation of viruses occurs during specific vector feeding behaviors, and feeding behavior varies greatly among insects with piercing-sucking mouthparts. In this review we provide an overview of the feeding behavior of the major insect vectors with piercing sucking mouthparts: aphids, whiteflies, mealybugs, hoppers, and thrips. We briefly review the different mechanisms of plant virus transmission by these insects, and discuss how each mechanism requires a vector that engages in specific feeding behaviors, and how differences in feeding behavior among these insects can determine which viruses they are capable of transmitting. We also discuss recent findings indicating that plant viruses can directly modify their vector's behavior in a way that enhances transmission to a host plant.